GAMBAR AN TINGKAT KECEMASAN TENAGA KESEHATAN DALAM MEMBERIKAN PELAYANAN DI MASA PANDEMI COVID-19 DI PUSKESMAS PAAL MERAH I KOTA JAMBI TAHUN 2021 - Akbidita, Putri; Aurora, Wahyu Indah Dewi; Herlambang, Herlambang (LPPM Universitas Jambi, 2023)
ABSTRACTBackground: The spread of the Covid-19 disease is growing very fast and has plagued almost all countries sothat health workers who are at the forefront in providing health services are very vulnerable to physical and mentalhealth risks such as anxiety. The purpose of this study was to describe the level of anxiety of health workers inproviding services during the Covid-19 pandemic.Methods: This study uses a sequential explanatory design. The sample of 33 respondents was taken by the totalsampling method.Results: The results showed that the anxiety level of health workers was not anxious, as many as 31 people(93.9%) and mild anxiety as many as 2 people (6.1%). Most of the respondents aged > 30 years were 26 people(78.8%), women 31 people (93.9%), the last education was DIII 21 people (63.6%), married 32 people (97%) andthe type of health workers are mostly midwives with a total of 10 people (30.3%).Conclusion: There is no anxiety for health workers because health workers can adapt, there are different phasesof the pandemic, efforts to implement health protocols, vaccinations, and social support.Keywords: Anxiety, Covid-19 Pandemic, Health WorkersABSTRAKLatar belakang: Penyebaran penyakit Covid-19 berkembang sangat cepat dan telah mewabah hampir ke seluruhnegara sehingga tenaga kesehatan yang berada di garda depan dalam memberikan pelayanan kesehatan sangatrentan terhadap risiko kesehatan fisik dan mental seperti kecemasan. Tujuan penelitian ini untuk mengetahuigambaran tingkat kecemasan tenaga kesehatan dalam memberikan pelayanan di masa pandemi Covid-19.Metode: Penelitian ini menggunakan desain sequential explanatory. Sampel sebanyak 33 responden diambildengan metode total sampling.Hasil: Hasil penelitian menunjukkan bahwa tingkat kecemasan tenaga kesehatan adalah tidak cemas yaitusebanyak 31 orang (93,9%) dan kecemasan ringan sebanyak 2 orang (6,1%). Sebagian besar responden berusia>30 tahun sebanyak 26 orang (78,8%), perempuan 31 orang (93,9%), pendidikan terakhir DIII 21 orang (63,6%),sudah menikah 32 orang (97%) dan jenis tenaga kesehatan mayoritas merupakan bidan berjumlah 10 orang(30,3%).Kesimpulan: Tidak cemasnya tenaga kesehatan karena tenaga kesehatan sudah dapat beradaptasi, adanyaperbedaan fase pandemi, upaya menerapkan protokol kesehatan, vaksinasi, dan dukungan sosial.Kata kunci: Kecemasan, Pandemi Covid-19, Tenaga Kesehatan